Bioavailability of insulin detemir and human insulin at the level of peripheral interstitial fluid in humans, assessed by open‐flow microperfusion. Issue 12 (9th October 2015) - Bodenlenz, M.; Ellmerer, M.; Schaupp, L.; Jacobsen, L. V.; Plank, J.; Brunner, G. A.; Wutte, A.; Aigner, B.; Mautner, S. I.; Pieber, T. R.
Abstract : Aims: To find an explanation for the lower potency of insulin detemir observed in humans compared with unmodified human insulin by investigating insulin detemir and human insulin concentrations directly at the level of peripheral insulin‐sensitive tissues in humans in vivo . Methods: Euglycaemic‐hyperinsulinaemic clamp experiments were performed in healthy volunteers. Human insulin was administered i.v. at 6 pmol/kg/min and insulin detemir at 60 pmol/kg/min, achieving a comparable steady‐state pharmacodynamic action. In addition, insulin detemir was doubled to 120 pmol/kg/min. Minimally invasive open‐flow microperfusion (OFM) sampling methodology was combined with inulin calibration to quantify human insulin and insulin detemir in the interstitial fluid (ISF) of subcutaneous adipose and skeletal muscle tissue. Results: The human insulin concentration in the ISF was ∼115 pmol/l or ∼30% of the serum concentration, whereas the insulin detemir concentration in the ISF was ∼680 pmol/l or ∼2% of the serum concentration. The molar insulin detemir interstitial concentration was five to six times higher than the human insulin interstitial concentration and metabolic clearance of insulin detemir from serum was substantially reduced compared with human insulin. Conclusions: OFM proved useful for target tissue measurements of human insulin and the analogue insulin detemir. Our tissue data confirm a highly effective retention of insulin detemir in the vascular compartment. The higher insulin detemir relative to human insulin tissue concentrations at comparable pharmacodynamics, however, indicate that the lower potency of insulin detemir in humans is attributable to a reduced effect in peripheral insulin‐sensitive tissues and is consistent with the reduced in vitro receptor affinity.